STRATEGY OF THE DISTRICT HEAD IN HANDLING PUBLIC ORDER AND PUBLIC TRANQUILITY DISTURBANCES AS AN IMPACT OF POPULATION MIGRATION IN JATINANGOR DISTRICT, SUMEDANG REGENCY - AGUST ALEXANDER NARANTERY; Sutiyo Sutiyo; Imelda Hutasoit (Jurnal Ilmu Pemerintahan Suara Khatulistiwa, 2026)
Population migration in Jatinangor District Sumedang Regency generates complex social dynamics affecting public order and community peace. As an educational and local economic hub Jatinangor attracts students workers and business actors leading to increased population density boarding house activities traffic congestion illegal parking environmental challenges and potential social conflicts and crime. This study describes the implementation of public order and community peace and formulates the District Head’s strategy in managing disturbances caused by population migration. A descriptive qualitative method was employed with data collected through interviews observation and document analysis. The strategy was analyzed using the ASOCA framework consisting of Ability Strength Opportunity Culture and Agility. This study contributes to public governance studies by demonstrating how the ASOCA framework can be applied for District level public order management in migration intensive educational areas. Findings indicate that while the District Head possesses coordination guidance and supervision capacities gaps remain in migrant registration and boarding house oversight. Apparatus capacity security posts patrol vehicles and CCTV support public order efforts though personnel facilities and budget remain limited. Universities community leaders youth groups and business actors offer strategic opportunities for collaboration. Mutual cooperation deliberation and tolerance remain important social capital though interaction between local residents and migrants is still limited. Complaint handling has begun but responses need more integration and consistency. Recommended strategies include integrating regulations and standard operating procedures strengthening collaboration with universities and communities optimizing complaint mechanisms reinforcing local social values and developing responsive dialogue based public services.